Emergency atrial septostomy with nasogastric tube through umbilical venous route in neonates with critical congenital heart defects - Kariyappa, Mallesh; Govindarajan, Varun; Hanumanna, Anil Kumar; Nagarasaiah, Ashwini Harohalli; Jagadish, Meghana (International Journal of Contemporary Pediatrics, 2021)
Neonates born with critical duct dependent congenital heart diseases acutely deteriorate in first few days after birth when physiological conduits which allow for mixing blood close. Balloon Atrial septostomy is performed on emergency basis in such neonates to create a right to left intracardiac shunt, until a definitive surgery is performed, but requires a cardiac intervention setup. In settings where advanced cardiac interventions are not available, we propose an alternative approach for atrial septostomy using nasogastric feeding tube through umbilical venous route, under echocardiographic guidance. Feeding tube gradually inserted into the umbilical vein, reaches the right atrium, following which it is thrust into the atrial septum at the location of foramen ovale, perforating it to create an emergency conduit between the atria. We performed the above procedure in a neonate with dTGA at our NICU setup, with partially successful outcome. We propose this method as an alternative, safe, simple and cost effective procedure, though not definitive, in resource limited settings for emergency stabilisation of neonates with critical duct dependent heart defects.